Evaluation of the bond strength of orthodontic brackets and the degree of polymerisation and microhardness of an orthodontic adhesive using polyvawe light curing unit and varying light densities - Topbasi, Nuri Mert; Benkli, Yasin Atakan (Brazilian Dental Science, 2020)
Objective: This study evaluates the shear bond strength (SBS) and Vickers micro-hardness (VHN) of the orthodontic adhesive resin Transbond XT using thermocycled samples. The study also measures the degree of cure by poliwave light curing unit Valo. Materials and Methods: 135 brackets were bonded for the SBS test, and 90 disc-shaped orthodontic adhesive resins were prepared for the VHN test. The measurements were taken either immediately or after 500 or 10.0000 thermocycling. The SBS and VHN test data were statistically evaluated using a Two-way ANOVA and Tukey multiple comparison tests. The degree of conversion (DC) was measured by FTIR. Results: The 10-sec polymerized control group (57.08) and the 10.000 termocycled samples (55.96) had the highest VHN scores. On the other hand, the 3 second polymerized and the 10.000 termocycled samples (39.22) had the lowest VHN scores. There was no significant difference in the bracket SBS values between the termocycled and immediate groups. An evaluation of the bond failure surfaces revealed that the ARI scores did not differ between the immediate and the thermo-cycled groups according to the power modes. The FTIR results revealed that the lowest DC was seen in the 3 second light-cured sample. Conclusion: Transbond XT provided sufficient bonding in terms of microhardness and DC under in vitro bracket bonding conditions after 10 and 8 seconds of Poliwave LED curing. However, low mean values were seen in the groups that received Poliwave LED curing for only 3 seconds. KEYWORDSARI score; FTIR; Light-Emitting Diode; Orthodontics; Thermocycling.